Analysis of Inclusive Agricultural Management Models for Strengthening Institutions and Mushroom Industry Performance - Edwin Pondi Suwanto; Vierkury Metyopandi; Arya Agung Al Aziz; Putri Ayu Setiyowati; Arbikhan Mustaan (Business Management Research, 2025)
This research aims to analyze the level of inclusivity in the mushroom industry management in Mojokerto Regency using the Agricultural Industry Inclusivity Management (IMIP) model and to identify factors influencing inclusivity. This study employed a quantitative approach with an explanatory design. Primary data were collected through a survey using a Likert- scale questionnaire administered to 60 respondents, comprising mushroom farmers and related business actors. The five dimensions of IMIP analyzed were participation, equitable access, benefit distribution, capability and innovation, and institutional connectivity. Data analysis was performed using descriptive statistics, Pearson correlation tests, and multiple linear regression with SPSS. The results indicate that the inclusivity level of the mushroom industry is in the "fairly good" category. The dimensions of participation and institutional connectivity were the most dominant factors influencing inclusivity (p<0,01), followed by equitable access and benefit distribution. Meanwhile, capability and innovation did not have a significant effect. The regression model explained 68% of the variation in mushroom industry inclusivity. These findings highlight the importance of strengthening collective participation, institutional networks, access to capital, and technical assistance to enhance the inclusivity and competitiveness of the mushroom industry in Mojokerto Regency.